2020
DOI: 10.1002/1873-3468.13962
|View full text |Cite
|
Sign up to set email alerts
|

Structural plasticity of substrate selection by activation‐induced cytidine deaminase as a regulator of its genome‐wide mutagenic activity

Abstract: Activation-induced cytidine deaminase (AID) mediates somatic hypermutation and class-switch recombination of antibodies. Computational-biochemical and crystallography analyses of AID have identified three surface grooves for binding single-stranded DNA (ssDNA). Functional studies have also found evidence for RNA-binding motifs on AID. Although AID and the related apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like (APO-BEC) enzymes share a conserved core, AID uniquely features multiple substrate-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Given the width of ds-DNA helix (~20 Å), the identified DNA binding groove on AID explained its substrate specificity for acting only on ssDNA and not dsDNA (190)(191)(192)(193). The presence of this DNA binding groove has been confirmed upon crystallization of Hs-AID with ssDNA (129,194).…”
Section: Comparative Evolutionary Analyses Of Aid In Cell-free Biochemical Assaysmentioning
confidence: 90%
See 2 more Smart Citations
“…Given the width of ds-DNA helix (~20 Å), the identified DNA binding groove on AID explained its substrate specificity for acting only on ssDNA and not dsDNA (190)(191)(192)(193). The presence of this DNA binding groove has been confirmed upon crystallization of Hs-AID with ssDNA (129,194).…”
Section: Comparative Evolutionary Analyses Of Aid In Cell-free Biochemical Assaysmentioning
confidence: 90%
“…Given the importance of proper positioning of dC inside the active site for efficient deamination activity, defining the secondary catalytic pocket residues was a step forward in solving the functional structure of AID. In the same work, we also described a novel structural regulatory mechanism of AID/APOBEC activity in that the majority of Hs-AID conformations at any given time contain catalytic pockets that are closed and inaccessible for accommodating a dC for deamination (194). Furthermore, we observed that the majority of ssDNA:AID binding events result in ssDNA bound non-productively on the surface in conformations that do not pass over the catalytic pocket, presumably due to the highly positively charged surface of AID (+11, the highest surface positive charge amongst AID/ APOBECs) (52,194).…”
Section: Comparative Evolutionary Analyses Of Aid In Cell-free Biochemical Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Encoded by a gene on chromosome 1, CDA normally catalyzes the irreversible hydrolytic deamination of free cytidine and deoxycytidine to uridine and deoxyuridine. Contrary to this CDA, the widely studied activation-induced CDA is encoded by a gene on chromosome 12; activationinduced CDA is necessary for generating antibody diversity, as it deaminates single strand-DNA causing mutations (22). CDA polymorphism and activity are potential predictive biomarkers for Gem (23,24).…”
Section: V1 Increases Gem Inactivation and Effluxmentioning
confidence: 99%
“…Though the core catalytic pocket arrangement and overall folding of AID/APOBEC3s is well conserved, the enzymes differ highly in their surface residue composition and dynamics. One such difference is the shape and location of ssDNA binding grooves: A3s typically have one well-defined ssDNA binding groove (54,55), while AID has evolved several nucleic acid binding regions (19,51,52,(56)(57)(58)(59). AID contains two ssDNA binding grooves that pass over the catalytic pocket (ssDNA binding groove 1 and 2) (51,52,56,57), an assistant patch located distally from the catalytic pocket that enhances structured DNA binding (57), and an RNA binding region involved in binding switch-region RNA transcripts (58).…”
Section: Introductionmentioning
confidence: 99%